Penguatan Empati dan Kerjasama Melalui Kegiatan Psikologi Sosial Bagi Karang Taruna di Desa Tanjung Lago - Itriyah Itriyah; Kemala Putri Anugerah (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
This community service program aims to strengthen empathy and cooperation through social psychology for youth organizations in Tanjung Lago village. The method used is the Interactive Lecture Method, which involves delivering basic material on empathy and cooperation in a clear and communicative manner to members of the youth organization. The results of this community service program show that it ran well and had a positive impact on participants. Social activities accompanied by psychological education can increase participants' understanding of the importance of empathy, caring, effective communication, and cooperation in youth organizations.